Analisis media yang digunakan dalam model pembelajaran game based learning untuk meningkatkan motivasi belajar IPS di MTs Ma’arif NU Kota Malang - azizah, siti nur (Maliki Interdisciplinary Journal, 2024)
One factor in low student learning outcomes is also caused by low student learning motivation. During social studies lessons, this also happened to students at MTs Ma’arif NU, Malang city. Therefore, to increase students’ learning motivation, an interesting and fun learning paradigm is needed. The aim of this research is to examine the media included in the game-based learning paradigm at MTS Ma’arif NU Malang City in order to increase students’ enthusiasm for learning social studies. This research uses a qualitative methodology with a theoretical approach, where the author refers to previous publications or journals to offer theoretical insight into the problem at hand. In addition, the author used MTS Ma’arif NU Malang City for observations and interviews for this research. In this research, the results showed that the various media used in the game-based learning model to increase students’ social sciences learning motivation at MTs Ma’arif NU Malang City were media in the form of Kahoot, Quizzizz and Wordwall. So, with the game-based learning model media, it can increase the motivation to learn social studies at MTs Ma’arif NU Malang City students.